Femoral neck fractures in non-geriatric patients: femoral neck system versus cannulated cancellous screw - Guy Romeo Kenmegne; Chang Zou; Yue Fang; Xuanhong He; Yixiang Lin; Yijie Yin (BMC Musculoskeletal Disorders, 2023)
Abstract Background The fractures of femoral neck account for 50% among hip fractures with around 3%-10% occurring in younger population of below 65 years. The newly introduced FNS as management approach appears to be a potential alternative to the traditional CCS. The aim of this study was to compare the clinical efficacy and outcome of the femoral neck system (FNS) and the cannulated cancellous screw (CCS) in the treatment of femoral neck fractures in adult below 65 years of age. Methods Data of 114 patients between 18–65 years, admitted in our department for femoral neck fracture from January 2019 to March 2021 were retrospectively studied and ranged into two groups based on the surgical methods: FNS group (56 patients) and CCS group (58 patients). The variables of interest including demographic and clinical variables (age, gender, fracture mechanism, injury side and classification), perioperative parameters(operation time, intraoperative bleeding, incision length and hospitalization time), postoperative outcomes and complications (fracture healing time, nonunion rate, femoral neck avascular necrosis, aseptic screw loosening and the Harris Hip Score), were analyzed and compared between the two groups. Results All 114 patients presented satisfactory reduction and were followed-up for a period of 12 to 36 months (mean 27 ± 2.07 months); there were no significant differences between both groups in terms of age, gender, fracture classification, side of injury, mechanism of injury, the operative time, intraoperative blood loss and the hospital length of stay. However, the fracture healing time between FNS group and CCS group was statistically significant (p < 0.05), respectively 2.86 ± 0.77 and 5.10 ± 0.81 months. The significant differences were also found in terms of numbers of fluoroscopies 8.34 ± 1.38 Vs 17.72 ± 2.19, the HHS 87.80 ± 1.92 Vs 84.28 ± 2.24, postoperative complications 8 (14.28%) Vs 26 (44.82) respectively in FNS and CCS group. Conclusion FNS presented satisfactory outcomes had significantly lower complications rate, therefore, can be one of the alternatives for internal implantation devices in treatment of femoral neck fracture in non-geriatric population.